Debriefing - What, why and how? - Vijayanand Jamalpuri; Amy Kline; Mike Shepherd (Wolters Kluwer Medknow Publications, 2016)
Debriefing is a critical part of a simulation exercise in order to foster reflection and enhance clinical reasoning. Without a proper understanding of how to debrief simulation based trainings or real life events can be ineffective and inconsistent. In this article we provide an overview to the necessary elements of debriefing. We describe a three-stage approach to debriefing; reactions, descriptive and summary and review different forms of questioning that can be used in the descriptive phase. It is important for educators in simulation to train and understand how to effectively lead learners through simulation and debriefing in order to be successful.